Integrating mechanisation in sustainable agricultural development strategies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Proceedings of a workshop, Ouagadougou, Burkina Faso, 1997.CTA, 1999. 312 pp.ISBN 92 9081 2109CTA No 951, 40 credit points